The Marilyn Monroe century - Miller, Joshua (Joshua Israel); Fortin, M. A. (Mark Alexandre), 1978- (Abrams Books, 2026)
"The Marilyn Monroe Century is a lavishly produced tribute to Marilyn Monroe on her 100th birthday, documenting her transformation from Norma Jeane to Marilyn Monroe through never-before-seen photographs and diary entries by Bernard of Hollywood." -- publisher website.